2014
DOI: 10.1007/s00259-013-2670-x
|View full text |Cite
|
Sign up to set email alerts
|

Individualized dosimetry-based activity reduction of 90Y-DOTATOC prevents severe and rapid kidney function deterioration from peptide receptor radionuclide therapy

Abstract: Purpose Assessment of kidney function evolution after 90 Y-DOTATOC peptide receptor radionuclide therapy (PRRT) with capped activity administration based on a 37-Gy threshold of biological effective dose (BED) to the kidney.Methods In a prospective phase II study, patients with metastasized neuroendocrine tumours were evaluated for therapy using 185 MBq 111 In-pentetreotide with amino acid coinfusion. Planar whole-body images were acquired at four time-points after injection and kidney volumes were measured El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…20, the BED TD 50/5 is 44 Gy (α/β = 2.5 Gy), and the threshold for radiation nephropathy is 33 Gy [14]. These results were applied in a prospective clinical trial [17], where 22 patients completed treatment with repeated cycles of 90 Y-DOTATOC with the aim of not exceeding an accumulated renal BED of 37 Gy (α/β = 2.5 Gy), showing no grade 3-4 toxicity at 18-month follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…20, the BED TD 50/5 is 44 Gy (α/β = 2.5 Gy), and the threshold for radiation nephropathy is 33 Gy [14]. These results were applied in a prospective clinical trial [17], where 22 patients completed treatment with repeated cycles of 90 Y-DOTATOC with the aim of not exceeding an accumulated renal BED of 37 Gy (α/β = 2.5 Gy), showing no grade 3-4 toxicity at 18-month follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…At 8 and 24 h postinjection, tomographic views (SPECT) were acquired from the dome of the liver downward, using the aforementioned gamma-camera, with a 128×128 matrix, 20 sec/view and 72 views over 360°. Only SPECT abdomen was performed in every patient since the kidneys, as critical organs during PRRT with 90 Y-DOTATOC, had to be in de FOV for dosimetric purposes [19]. On the other hand, most of these study patients had the majority of their tumoral lesions in the abdomen (liver, mesenterium, retroperitoneum, vertebral bone metastases).…”
mentioning
confidence: 99%
“…These findings were confirmed by a prospective phase 2 dosimetry trial in which a threshold of BED of 37 Gy for kidney toxicity was found to be a good guide for 90 Y-DOTATOC PRRT (50).…”
Section: Prrt With 90 Ymentioning
confidence: 63%